2012
DOI: 10.1038/jcbfm.2012.28
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor Prolyl Hydroxylase Inhibition: Robust New Target or Another Big Bust for Stroke Therapeutics?

Abstract: A major challenge in developing stroke therapeutics that augment adaptive pathways to stress has been to identify targets that can activate compensatory programs without inducing or adding to the stress of injury. In this regard, hypoxia-inducible factor prolyl hydroxylases (HIF PHDs) are central gatekeepers of posttranscriptional and transcriptional adaptation to hypoxia, oxidative stress, and excitotoxicity. Indeed, some of the known salutary effects of putative 'antioxidant' iron chelators in ischemic and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 113 publications
(126 reference statements)
1
70
0
1
Order By: Relevance
“…Non-specific PHD inhibitors are neuroprotective in acute neurotoxic settings such as stroke (Karuppagounder and Ratan, 2012; Nagel et al, 2010; Quaegebeur and Carmeliet, 2010). However, their lack of specificity and the increased risk of eliciting adverse effects when blocking various dioxygenases render clinical translation more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Non-specific PHD inhibitors are neuroprotective in acute neurotoxic settings such as stroke (Karuppagounder and Ratan, 2012; Nagel et al, 2010; Quaegebeur and Carmeliet, 2010). However, their lack of specificity and the increased risk of eliciting adverse effects when blocking various dioxygenases render clinical translation more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…44 Furthermore, HIF-prolyl hydroxylases may indirectly regulate VEGF through their effects on EPO, which in turn stimulates production of VEGF. 45 The clinical relevance of potential effects of VEGF elevation is not known.…”
Section: Discussionmentioning
confidence: 99%
“…15 In brain trauma, HIF-1α has a key role in brain edema formation and BBB disruption via a molecular pathway involving MMP-9. 16 A recent study showed that hypoxia-induced MMP-9 expression leads to vascular leakage, which could be reduced by MMP inhibition.…”
Section: Introductionmentioning
confidence: 99%